Analisis Komparatif Kinerja Keuangan: Studi Kasus Primaya Dan Pt Sarana Meditama Metropolitan Pada Periode 2021-2024 - Yudiantono, Ade Heli; Dwimelissa, Reisha; Sumiati, Sumiati; Pusvita, Ratna; Ramadhan , Yanuar (Riviera Publishing, 2025)
This study aims to analyze and compare the financial performance of two companies in the Indonesian health sector, namely Primaya and PT Sarana Meditama Metropolitan (SMM) during the 2021-2024 period. Using a financial ratio analysis approach, this study evaluates the aspects of liquidity, profitability, solvency, operational efficiency, and market valuation of the two companies. The results show that Primaya has significant advantages in terms of liquidity, profitability, and operational efficiency, while SMM shows a more conservative approach in capital structure and more efficient receivables management. The implications of this study provide insights for investors, creditors, and other stakeholders in strategic decision-making related to investment and performance appraisal in Indonesia's health sector.